PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA PEGAWAI PADA DEPUTI BIDANG PENGEMBANGAN PEMUDA DI KEMENTERIAN PEMUDA DAN OLAHRAGA - Rahayu Rahayu; Henny Delisda Nasution (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This study is intended to determine the extent to which leadership style and motivation affect the work discipline of Deputy Youth Development employees at the Ministry of Youth and Sports. The research method used is a survey research method with data collection techniques through a questionnaire. A sample of 115 employees was obtained using the sample collection method through the saturated sample method. Data collection is done by collecting primary data through distributing questionnaires and taking secondary data sources through books, literature, internet and lecture materials. Multavariate Structural Equation Model (SEM) technique was used in this study to analyze data statistically. The results showed that the leadership style and motivation variables had a significant influence on the employee work discipline variables.